KOMPARASI PEMAHAMAN KONSEP SISWA KELAS X MELALUI MEDIA TEKNOLOGI DAN KONVENSIONAL DI SMAN 4 KARAWANG - Lulu Salsabilah; Muthia Hanifa Nugraha; Ilham Mukhtar Sya’bani; Muhammad Fadly Albahri; Maharani Maharani (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2026)
This study aims to compare the conceptual understanding of Grade X students using technology-based media with those using conventional learning methods at SMAN 4 Karawang. The study employed a quasi-experimental method with a non-equivalent control group design. The research subjects consisted of two classes, namely Class X.6 as the experimental group (36 students) receiving technology-based learning, and Class X.1 as the control group (34 students) receiving conventional learning. Data were collected through pre-test and post-test multiple-choice instruments. Data analysis used the N-Gain score to measure the improvement in conceptual understanding of each group. The results showed that the average N-Gain score of the control class (0.033) was slightly higher than that of the experimental class (-0.079), with both categorized as low. The average post-test score of the control class reached 0.699, while the experimental class reached 0.688. These findings indicate that, within the context of this study, the use of technology-based media has not been proven significantly more effective than conventional methods in improving students’ conceptual understanding. Further studies are needed regarding the design and implementation of technology-based media to maximize its potential in the learning process.